Indonesia KERANGKA KONSEPTUAL: PENERAPAN TEORI ANTRIAN (M/M/1 WITH FINITE SOURCE) DALAM MEMINIMALISIR DEMURRAGE (STUDI KASUS PELAYANAN PEMUATAN KLINKER EKSPOR PT. QWE) - Arianto, Mahdar; Yunani, Akhmad; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (FEB Universitas Sam Ratulangi Manado, 2024)
Problem of the time used in loading cargo at the port is sometimes not in accordance with the agreement agreed upon by the charterer and the shipowner. The impact that arises on the company is due to the emergence of demurrage. Therefore, in the case of PT QWE's export clinker loading service, it is proposed to apply the M/M/1 queuing theory with finite sources to minimize demurrage through queue arrangements for cargo delivery by trucks where the truck is assumed to contribute a lot to loading delays so far. This conceptual framework is descriptive research with a simulated quantitative approach. This conceptual framework provides a proposal to apply queuing theory with the M/M/1 with finite source model calculated using the Pom Qm application with the aim of minimizing demurrage through the arrangement of cargo delivery trucks, then simulated to get the optimal value by calculating operational costs. The research results of this conceptual framework are expected to have a positive impact on minimizing demurrage and are also expected to cause despatch and profit from efficient operational costs.